High-Resolution Episcopic Imaging for Visualization of Dermal Arteries and Nerves of the Auricular Cymba Conchae in Humans - Dabiri, Babak; Kampusch, Stefan; Geyer, Stefan H.; Le, Van Hoang; Weninger, Wolfgang J.; Széles, Jozsef Constantin; Kaniusas, Eugenijus (Frontiers in Neuroanatomy, 2020)
Therapeutic applications of auricular vagus nerve stimulation have drawn recent attention. Since the targeted stimulation process and parameters depend on the electrode-tissue interaction, the lack of structural anatomical information on innervation and vascularization of the auricle restrain the current optimization of stimulation paradigms. For the first time, we employed high-resolution episcopic imaging (HREM) to generate histologic volume data from donated human cadaver ears. Optimal parameters for specimen preparation were evaluated. Anatomical 3D vascular and nerve structures were reconstructed in one sample of an auricular cymba conchae (CC). The feasibility of HREM to visualize anatomical structures was assessed in that diameters, occupied areas, volumes, and mutual distances between auricular arteries, nerves, and veins were registered. The selected region of CC (3 x 5.5 mm) showed in its cross-sections 21.7 ± 2.7 (mean ± standard deviation) arteries and 14.66± 2.74 nerve fibers. Identified nerve diameters were 33.66±21.71 µm, arteries had diameters in the range of 71.58±80.70 µm. The respective occupied area showed a share of in average 2.71% and 0.3% for arteries and nerves, respectively, and similar volume occupancy for arteries and nerves. Inter-centroid minimum distance between arteries and nerves was 274±222 µm. The density of vessels and nerves around a point within CC on a given grid was assessed, showing that 50% of all vessels and nerves were found in a radial distance of 1.6-1.8 mm from any of these points, which is strategically relevant when using stimulation needles in the auricle for excitation of nerves. HREM seems suitable for anatomical studies of the human ear. A 3D model of CC was established in the micrometer scale, which forms the basis for future optimization of the auricular vagus nerve stimulation. Obviously, the presented single cadaver study needs to be validated by additional anatomical data on the innervation and vascularization of the auricle.